Size-Dependent Oxidation Mechanism of Supported Pd Nanoparticles - Libuda, Jörg; et al. (Angewandte Chemie International Edition, 2006)
The oxidation and reduction of Fe3O4-supported Pd nanoparticles is strongly size-dependent and implies that the oxidation mechanism is controlled by the metal oxide interface. Molecular beam experiments and scanning tunneling microscopy indicate that this size dependence gives rise to a pronounced maximum of the oxygen-storage capacity as a function of metal loading. (Graph Presented) © 2006 Wiley-VCH Verlag GmbH & Co. KGaA.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.ppc20.sizede
Keywords: Heterogeneous catalysis; Nanoparticles; Oxidation; Palladium; Surface chemistry